Kebijakan Kriminalisasi Perbuatan Menyetubuhi Mayat Dalam Hukum Pidana Indonesia - Valeta, Echa; Erdianto, Erdianto; Ardiyanto, Syaifullah Yophi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study aims to examine the policy of criminalizing sexual intercourse with corpses within the framework of Indonesian criminal law. The primary focus lies in comparing the old Criminal Code, which did not explicitly regulate such acts (only through Article 181 on mistreatment of corpses), with the new Criminal Code, which explicitly criminalizes the act under Article 271. Employing a normative juridical approach, this research is analyzed using the principles of legality, the theory of culpability, and supported by non-legal theories such as morality, legal sociology, and forensic psychology to strengthen the rationale for criminalization. The findings demonstrate that penalizing sexual acts with corpses is legally justifiable, both from the perspective of substantive and procedural criminal law, as it reflects the protection of human dignity even after death. This study also identifies several challenges in the implementation, including low public awareness and evidentiary difficulties, and proposes enhancing legal education and inter-agency collaboration as potential solutions. The research contributes to the development of a more humanistic and responsive Indonesian criminal law in addressing contemporary crimes.